Metsäpaviljonski, Form Follows Wood - Suau, Cristian (Docomomo Journal, 2012)
Nowadays, the emphasis in the design of exposition pavilions is mainly full of pseudo–technical or rhetorical ideas of progress. Nevertheless most of them do not communicate a vision. They show a lack of spatial qualities and continuity with the built environment. In general, there is not a common conservation agenda to adapt or reuse exemplary Modern Pavilions. Some emblematic cases are haunted icons, a consequence of undocumented, incorrect or simply fake reconstruction, whilst others are victims of neglectfulness and degradation. Nevertheless, what can we still rediscover by reviving or reconstructing Modern Movement Exposition pavilions? During the 1930s, pavilions were not only visionary and experimental manifestations of living systems but were also temporary and fast–built showrooms disseminating a cultural or ideological message.